(untitled) (Conversatoria Linguistica, 2019)
The purpose of the study was to examine and evaluate the communication abilities of a girl who was diagnosed with early autism. To further analyze the case study, it was necessary to examine the interactions and communication skills of the child. The study was designed to help verify how the girl communicates with other people at what level her communication and language skills developed. For this action, it was necessary to focus on several important issues, as: o Interactive behaviors – how the interview structure looks, what are the ways toinitiate and respond to messages, o Communication behaviors – how are the relationships between verbal and non-verbal behaviors and the intentions being made, o Speech language – which language the child uses during the conversation. The conclusion is: the language abilities of an autistic child are limited, resulting in delay or lack of speech, difficulty in learning grammar rules, low vocabulary.